Using planktonic species as model organisms for understanding biological invasion dynamics in a changing world - Macêdo, Rafael Lacerda (Universidade Federal de São Carlos, 2022)
The ability of species to become invasive (ie, species invasiveness) can be investigated through multiple approaches based on ecological and evolutionary characteristics associated with the ability of species to overcome a series of barriers and filters until proper invasion. Until now, formal attempts aiming to define plankton invasions based on niche and whether invasive plankton species reliably respond to environmental parameters are overlooked. Therefore, in this study we analyzed the correlation between the occurrence of invasive and potentially invasive species in plankton and environmental variables, including future climatic alterations, and habitat features. We applied species distribution models for the species and reconstructed the niche spaces occupied using different approaches and algorithms considering their invasion history and invasion processes. We tested the hypothesis of niche conservatism and predicted suitable areas for future invasions of non-native species: Ceratium furcoides (dinoflagellate), Moina macrocopa and Cercopagis pengoi (cladocerans). In addition, we described and modeled the global social-economic costs of planktonic invasive species using the most comprehensible database – the INVACOST. Notably, all models reliably supported our hypotheses allowing three main conclusions: (i) Niche shift was detected for one species C. furcoides, while niche unfilling was found for the M. macrocopa and C. pengoi, requiring further investigations on that species regarding evolutionary aspects favoring their expansion; (ii) Future environmental climate allow processes of expansion and colonization in highly disturbed environments such as hydroeletrical reservoirs and temporary ponds. (iii) Impact assessments needs improvement as both taxonomic and geographic gaps exist for the social economic costs of plankton invasions globally. Based on our findings, we strongly believe that these perspectives can contribute to increasing knowledge of the mechanisms that drive plankton invasions, to point the direction for which species and environments need more attention, and to rise novel hypotheses on the invasion processes of fast-evolving planktonic organisms.
Utilizando espécies planctônicas como organismos modelo para o entendimento da dinâmica das invasões biológicas em um mundo em mudanças
Keywords: Non-native cladocerans; Invasive dinoflagellate; Plankton invasiveness; Niche dynamics; Economic costs; Cladóceros não-nativos; Dinoflagelado invasor; Invasividade do plâncton; Dinâmica de nicho; Custos econômicos; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS